APPLICATION OF DELONE & MCLEAN MODEL TO ANALYZE SUCCESS OF DYNAMIC UNIVERSITY REPOSITORY WEBSITE - Kuncoro, Nico Stephanus; wati, Sulistio; Soebijono, Tony (Jurnal Sistem Informasi Universitas Dinamika, 2022)
Abstract: Dinamika University (Undika) is a private university located in Surabaya. It has two faculties, namely the Faculty of Technology and Informatics (FTI), the Faculty of Economics and Business (FEB), and the Faculty of Design and Creative Industries (FDIK). To support the learning process, Undika has various learning facilities and one of them is a library. The library at Undika itself has four online services in the form of a website, one of which is repository.dinamika.ac.id. This website contains information on a collection of scientific works related to the work of the academic community that can be accessed by anyone. in 2020 the whole world including Indonesia will experience a pandemic, so that the learning process and services in the field of education are carried out online, so that the repository.dinamika.ac.id website service needs to be optimized. This is supported by graphical data on the number of visitors to the repository website, which in 2020 did not increase significantly. Therefore, in this study, an evaluation of the repository.dinamika.ac.id website was carried out with the DeLone and McLean model by distributing questionnaires to 88 respondents from Dinamika University students, then a descriptive analysis of each variable was carried out. The results of the descriptive analysis obtained the average value of each variable. For system quality variables, an average of 3.76 is obtained which means close to good, for information quality 3.63 which means close to good, for service quality 3.60 which means close to good, for use 3.55 which means close to good, for user satisfaction 3.68 which means close to good, for net benefits 3.5 which means close to good. From the total of each variable obtained an average of 3.62 which means it is close to good. The results of the inferential analysis show that from the results of the hypothesis analysis above, which have a significant influence between variables to other variables, namely: the use variable affects the User Satisfaction variable by 34.6%, the user satisfaction variable affects the Net Benefit variable by 45.6%, Usage variable has an effect on the Net Benefit variable by 41.9%, and the Information Quality variable has an effect on the User Satisfaction variable by 49%.